Late onset of pneumothorax after bronchoscopic lung volume reduction due to migration of a nitinol coil. (27th November 2017) - Mongelli, Francesco; Cafarotti, Stefano; Di Giuseppe, Matteo; Patella, Miriam
Abstract: The use of Endobronchial coils are a relatively new brochoscopic technique for lung volume reduction. They appear to be safe and effective in improving quality of life, reducing morbidity and mortality related to the primary disease, while avoiding the many risks of morbidity and mortality associated with surgery. Nevertheless, some complications, such as pneumothorax, are relatively common in the periprocedural period. We describe a case of pneumothorax that occurred several days after brochoscopic technique for lung volume reduction due to direct perforation of the visceral pleura by a coil. The patient presented with a large pneumothorax associated with significant air leak, requiring surgical intervention. Exploration of the chest cavity showed a pleural tear caused by a coil. To our knowledge, this is an adverse event that has never been described before, suggesting the possible migration of the coil from the original position.